Transformasi fungsi public relation dalam penguatan literasi keuangan syariah di era disrupsi teknologi - azzahra, fathia (Maliki Interdisciplinary Journal, 2025)
The rapid growth of digital technology has significantly transformed the function of Public Relations (PR), particularly within Islamic financial institutions. This article explores PR’s strategic role in strengthening Islamic financial literacy amid the era of technological disruption. Through digital communication approaches, PR not only builds the institution’s image and reputation but also serves as an effective medium for public education. By utilizing social media, educational content, and influencer collaborations, PR helps enhance public understanding of Islamic financial principles and foster greater trust in Sharia-based institutions. This transformation highlights PR’s essential role in promoting inclusive and sustainable financial literacy. The study emphasizes that the success of Islamic financial literacy in the digital era depends on communication innovation, message credibility, and PR’s ability to adapt its strategies to the characteristics of modern generations.